Rising obesity-related hospital admissions among children and young people in England: national time trends study. - Jessica D Jones Nielsen; Anthony A Laverty; Christopher Millett; Arch G Mainous; Azeem Majeed; Sonia Saxena (PLoS ONE)
Objective To describe the trends in hospital admissions associated with obesity as a primary diagnosis and comorbidity, and bariatric surgery procedures among children and young people in England. Design National time trends study of hospital admissions data between 2000 and 2009. Participants Children and young people aged 5 to 19 years who were admitted to hospital with any diagnosis of obesity. Main outcome measures Age- and sex-specific admission rates per million children. Results Between 2000 and 2009, age- and sex-specific hospital admission rates in 5-19 year olds for total obesity-related diagnoses increased more than four-fold from 93.0 (95% CI 86.0 to 100.0) per million children to 414.0 (95% CI 410.7 to 417.5) per million children, largely due to rising admissions where obesity was mentioned as a co-morbidity. The median age of admission to hospital over the study period was 14.0 years; 5,566 (26.7%) admissions were for obesity and 15,319 (73.3%) mentioned obesity as a comorbidity. Admissions were more common in girls than boys (56.2% v 43.8%). The most common reasons for admission where obesity was a comorbid condition were sleep apnoea, asthma, and complications of pregnancy. The number of bariatric surgery procedures has risen from 1 per year in 2000 to 31 in 2009, with the majority were performed in obese girls (75.6%) aged 13-19 years. Conclusions Hospital admission rates for obesity and related comorbid conditions have increased more than four-fold over the past decade amongst children and young people. Although some of the increase is likely to be due to improved case ascertainment, conditions associated with obesity in children and young people are imposing greater challenges for health care providers in English hospitals. Most inpatient care is directed at dealing with associated conditions rather than primary assessment and management of obesity itself.